TULASI (OCIUM SANTUM) IN DENTISTRY- AN OVERLOOK - Rath, *Sunil Kumar; kirti bhuyan, Sriram; Sabyasachi Swain, Choudhury; Manaswini Panda, Subhashree (International Journal of Ayurveda and Pharma Research, 2017)
Tulasi, ’the holy basil is a prominent herb, that is used since the Vedic era as medicine. Currently many more systemic condition are cured through the use of various parts of this plant. This plant can be used for various diseases for treatment and maintenance of health. The oral health which could be called as indicator of systemic health is much more influenced by the use of this plant extracts. Method- The phrase â€œ Tulasi in dentistryâ€ was searched in Google Scholar, Pubmed. 37 article were selected through criteria of inclusion, from there we selected 17 articles according to exclusion criteria. So here in this article, the pharmacology of various parts of this plant and its use in dentistry, is explained. For health practitioners it is very useful to know the interaction of this plant with other drugs for smoothening of treatment. Conclusion- THE study emphasized the use of various parts of the plant in dental use for treatment of diseases like caries, mucosal lesions and periodontal pathology. Along with that it can be used in root canal therapy as disinfectant irrigation. Further study is required to prescribe these extracts in dentistry.